Patterns of COVID-19 induced bio-medical waste management in Bangladesh: a case study of Chittagong port city - Iqbal, Sarwar M.; Ashraf, Mahfuz; Nasreen, Akter; Shahidul, Islam M.; Faria, Sultana; Shamsal, Islam M. (International Journal Of Community Medicine And Public Health, 2023)
Background: The objective of this study was to investigate effective waste management practices and develop environment-friendly public health guidelines for the target audience. Methods: A cross-sectional descriptive study was conducted in 14 Upazilas of Chittagong Districts, where 200 community members were physically interviewed during the pandemic. Univariate, bivariate, and multivariate statistical analyses were conducted. Results: The majority of respondents followed government guidelines for waste management, and plastic containers, poly bags, bio-hazard bags, and metal containers were commonly used to collect waste. The type of container used was significantly associated with the level of education among community members. Non-environmental materials were used to deposit and dispose of COVID-19-induced biomedical waste. The majority of respondents had poor practices regarding the disposal of biomedical waste and were unaware of the standard duration for the disposal of infectious waste. The level of education was associated with awareness of COVID-19 rules and regulations. The recording of COVID-19-induced biomedical waste was insufficient, and the most commonly used methods for treating biomedical waste were biological, thermal, and irradiation. Plastic containers were the most frequently used disposal method for waste during COVID-19, which is hazardous to both the environment and public health. Conclusions: Community-based BCC activities by engaging community stakeholders in disseminating and raising awareness of key behaviors related to the environment and public health that are impacted by the biomedical waste in the community setting.